2003
DOI: 10.36440/recmvz.v6i1/3.3263
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do método de ensino da técnica cirúrgica utilizando cadáveres quimicamente preservados

Abstract: Objetivo: Avaliar o treinamento cirúrgico em cadáveres quimicamente preservados oferecido pelas Disciplinas de Técnica Cirúrgica e de Ortopedia, da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo (FMVZ/USP), São Paulo, SP, como método alternativo ao uso de animais vivos em aulas. Material e Método: Utilizou-se a Solução de Larssen modificada, que preserva as características dos animais como cor, consistência e textura dos tecidos e flexibilidade das articulações o mais semelhante pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 0 publications
1
10
0
8
Order By: Relevance
“…Veterinary schools have sought to associate the training using cadavers with training using live animals in caregiving in veterinary hospitals (BAUER, 1993;PAVLETIC et al, 1994). The same situation prevails in veterinary medicine undergraduate course in FMVZ / USP with wide acceptance from students, as observed by Silva (2003).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Veterinary schools have sought to associate the training using cadavers with training using live animals in caregiving in veterinary hospitals (BAUER, 1993;PAVLETIC et al, 1994). The same situation prevails in veterinary medicine undergraduate course in FMVZ / USP with wide acceptance from students, as observed by Silva (2003).…”
Section: Discussionsupporting
confidence: 56%
“…The results obtained showed that the training with chemically preserved dog cadavers combines the development of surgical techniques and psychomotor skills, as stated by Silva (2003), Silva;Ribeiro (2004), and Matera (2008) as they affirmed that the more realistic organoleptic characteristics of the cadaver used, as obtained through appropriate techniques of preservation and storage, the better is the training.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations